The Effect Of Audio Visual Health Education On The Anxiety Level Of Pre-Operative Patients With Spinal Anesthesia At Hj. Anna Lasmanah Banjarnegara Hospital - Zetra Irawan, Aditha; Lintang Suryani, Roro; Utami, Tin (Global Indonesia Health Care (GOICARE), 2023)
Purposive: Determine the effect of audio-visual health education using video media about spinal anesthesia on the anxiety level of preoperative patients with spinal anesthesia at Hj. Anna Lasmanah Banjarnegara hospital. Methods: This type of research is pre experiment pre test and post test with one group design. The sample technique in this study used purposive sampling of 92 pre-anesthesia patients. Data were taken using measurements of anxiety before and after provision of audio visuals on spinal anesthesia. This research instrument used questionnaires and audio visual media. Result: Before being given audio-visual health education spinal anesthesia most respondents experienced moderate anxiety of 45.7% and after being given some respondents experienced mild anxiety of 51.1%. The results of this study showed that there was an effect of providing audio-visual health education on the anxiety level of preoperative patients with spinal anesthesia as evidenced by a p value of 0.000 (0.000 0.005. Conclusion: There is an effect of providing audiovisual health education on the anxiety level of preoperative patients with spinal anesthesia at Hj. Anna Lasmanah Banjarnegara hospital.